The Effect of Daily Text Message Intervention on Antiretroviral (ARV) Treatment Compliance in Pregnant Women Infected with HIV - Eftyaningrum Dwi Wahyu Astutik; Yustika Rahmawati Pratami; Hasnia Hasnia; Susi Lestari; Endah Purwanti Handayani; Pranita Kartika Candra (GLOBAL HEALTH SCIENCE GROUP, 2026)
Compliance Antiretroviral (ARV) treatment in mothers pregnant women infected with HIV are component important in prevent HIV transmission from Mother to children and achieve viral load suppression. However, various factor like effect side medication, lack of knowledge, stigma, and duration treatment can lower compliance patients. Objective to know influence Daily Text Message intervention on compliance ARV treatment in mothers HIV-infected pregnant women at the Community Health Center Sentani Jayapura Regency. Research use design Quasy Experimental with Pretest-Posttest with Control Group Design on 30 selected respondents through consecutive sampling. Compliance measured use Morisky Medication Adherence Scale (MMAS-8) questionnaire. Analysis using the Wilcoxon test, Spearman correlation, and multiple linear regression. The content validity of the instrument was ensured through the use of a standardized and previously validated MMAS-8. Instrument reliability was supported by prior studies reporting a Cronbach’s alpha of ≥ 0.80. Although reliability was not re-tested due to the limited sample size, consistent use of the same instrument during pretest and posttest supported measurement reliability. The majority respondents own level compliance high (44%). There is difference significant between mark compliance before and after intervention in groups treatment (p=0.000). The Daily Text Message intervention increased compliance ARV treatment compared group control. Educational factors, effects side medication, and duration of treatment participate influence change MMAS-8 scores. Effective increase compliance ARV treatment in mothers pregnant women infected with HIV. Message text daily can become a supporting strategy for the PPIA program strengthen compliance treatment term long.